Corporate Performance: Evolution of the Concept and Strategies for Research Development - Iskandar, Bryan Carlo; Colline, Fredella (AIBPM Publisher, 2025)
This study aims to explore the development patterns, intellectual structure, and future research directions in the field of corporate performance using a bibliometric analysis approach. Drawing on 654 articles indexed in Scopus between 2015 and 2024, this research identifies major trends in publication productivity, citation dynamics, authorship, journal contributions, and country-level research outputs. The results reveal that the concept of corporate performance has evolved beyond traditional financial measures, encompassing governance quality, sustainability practices, and digital innovation. Through science mapping, three dominant research domains were identified: Governance Performance, Sustainable Management, and Sustainable Finance, highlighting the multidimensional nature of corporate performance. Achieving sustainable corporate performance requires integrating strong governance mechanisms, adopting sustainability principles, and embracing technological advancements. The findings suggest that future studies should employ cross-disciplinary approaches, incorporate ESG indicators, and leverage big data analytics to address the complexities of corporate environments. This study provides valuable insights for academics and practitioners by offering a comprehensive view of the field's evolution and proposing strategic directions to strengthen future corporate performance research and practice.